Perspektif Gender Dalam Novel Suti Karya Sapardi Djoko Damono : Tinjauan Feminisme Sastra Dan Implementasinya Pada Pembelajaran Sastra Di Sma - Rahman, Aditya, Prof. Dr. Ali Imron Al Ma'ruf, M. Hum (2017)
This study aims to (1) describe the background of the author of the novel Suti sosiohistoris sapardi djoko damono work, (2) Describe the structure of the building in Suti novel sapardi djoko damono work, (3) Describe the gender perspective contained in the novel Suti sapardi djoko damono work, (4) Describe the implementation of novel research results Suti sapardi djoko damono work. The object of this study is the gender perspective in the work Suti sapardi djoko damono with feminism literature review. This research uses descriptive qualitative research methods and strategies used in this study is a case study spikes. The data in this study are the words and sentences. The data source of this research is the novel Suti sapardi djoko damono work. Data analysis techniques in this study using a model reading semiotic reading of heuristic and hermeneutic. The results of this study are four (1) sapardi djoko damono born in Surakarta March 20, 1940. Besides being known as a writer he was also known as an academic. (2) The constituent elements of which are novel theme, the facts of the story, characterizations, plot, setting and literary devices. The theme tells of the struggle of women leaders in the community peranya still not optimal and also get injustice. (3) a gender perspective in the novel Suti include the role of women in public areas, marginalization of women, the subordination of women, the stereotype of women, violence, and workload. (4) the results of the research can be implemented on learning in high school literature class XI first half competence standards 7.memahami various tales, novels Indonesia / novel translation and basic competencies 7.2 analyzing the elements of intrinsic and extrinsic novel Indonesia / translation. Moral values contained in Suti novel can also be used as a means of forming the personality for learners.